2011
DOI: 10.1007/s00705-011-0955-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity among bovine leukemia viruses in Japan and their relationship to leukemogenicity

Abstract: Bovine leukemia virus (BLV) infection in cattle causes persistent lymphocytosis, and a few percent of infected animals develop lymphoid tumors, namely enzootic bovine leukosis (EBL). In this study, a 440-bp fragment of the env gene was amplified from 204 tumor samples collected from different regions of Japan and analyzed by restriction fragment length polymorphism (RFLP) to determine the association of BLV with EBL. Of the seven RFLP types defined, types I, II, and III were dominant and found in 12.7, 75.0, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
9
0
7
Order By: Relevance
“…Its topology confirmed the separate genotypes reported by these cited authors. Discussions and controversies have been generated concerning the number of genotypes of BLV but have evolved to consensus on the existence of at least seven genotypes, based both on studies using PCR-RFLP and those employing sequencing analyzes [24, 30, 32]. However, evidence for an eighth genotype was reported by Hemmatzadeh [33] and suggested by Matsumura et al [31], which is why it was considered by this study.…”
Section: Resultsmentioning
confidence: 77%
“…Its topology confirmed the separate genotypes reported by these cited authors. Discussions and controversies have been generated concerning the number of genotypes of BLV but have evolved to consensus on the existence of at least seven genotypes, based both on studies using PCR-RFLP and those employing sequencing analyzes [24, 30, 32]. However, evidence for an eighth genotype was reported by Hemmatzadeh [33] and suggested by Matsumura et al [31], which is why it was considered by this study.…”
Section: Resultsmentioning
confidence: 77%
“…Vertical transmission of BLV in cattle across the placenta or through colostrums has been previously reported [16]. Horizontal transmission of BLV has also been reported, which can occur with hematophagous insect bites or inappropriate medical treatment [12,14]. One report described the use of molecular techniques to show how hemoplasma could be transmitted vertically and horizontally in cattle [11].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations conferred some differences in restriction enzyme sites allowing the classification of BLV isolates into three [14] and six [15] genotypes by RFLP analysis. It was also demonstrated that some genotypes can influence the leukomogenecity of a virus [16]. Fechner et al [14] reported the association between some BLV variants and the failure of antibody detection in infected cattle; however, Licursi et al [15] and Asfaw et al [17], did not observe a relationship between particular genotypes and the serological status of infected animals.…”
Section: Introductionmentioning
confidence: 99%